Homologous recombination between overlapping thymidine kinase gene fragments stably inserted into a mouse cell genome. - Lin, F L (1984)
We have constructed a substrate to study homologous recombination between adjacent segments of chromosomal DNA. This substrate, designated lambda tk2 , consists of one completely defective and one partially defective herpes simplex virus thymidine kinase (tk) gene cloned in bacteriophage lambda DNA. The two genes have homologous 984-base-pair sequences and are separated by 3 kilobases of largely vector DNA. When lambda tk2 DNA was transferred into mouse LMtk- cells by the calcium phosphate method, rare TK+ transformants were obtained that contained many (greater than 40) copies of the unrecombined DNA. Tk- revertants, which had lost most of the copies of unrecombined DNA, were isolated from these TK+-transformed lines. Two of these Tk- lines were further studied by analysis of their reversion back to the Tk+ phenotype. They generated ca. 200 Tk+ revertants per 10(8) cells after growth in nonselecting medium for 5 days. All of these Tk+ revertants have an intact tk gene reconstructed by homologous recombination; they also retain various amounts of unrecombined lambda tk2 DNA. Southern blot analysis suggested that at least some of the recombination events involve unequal sister chromatid exchanges. We also tested three agents, mitomycin C, 12-O-tetradecanoyl-phorbol-13-acetate, and mezerein, that are thought to stimulate recombination to determine whether they affect the reversion from Tk- to Tk+. Only mitomycin C increased the number of Tk+ revertants.